Human Impacts of Economic Changes: Labor Productivity in North Macedonia 1991-2024 (Balkan Economies Structure, Transition and Transformation of North Macedonia, 1991-2024, 2025)
Productivity is one of the most important factors influencing the economic de-velopment of a country. It constitutes a key indicator of the efficiency in utilizing resources and the efforts of an economy to produce more output with fewer re-sources. Hence, determining the factors that affect the labour productivity rep-resent a challenging task. Productivity measures production efficiency, showing how many goods or services are created for a given resource unit. Productivity is usually measured as the ratio between output (what is produced) and input (the resources used, such as time, labor, and materials). Productivity is important because it helps increase efficiency and improve market competitiveness. An in-crease in productivity can lead to higher profits and improved living standards. In North Macedonia, productivity has experienced slow growth in some sectors, while certain industries have shown significant potential for improvement. This chapter will include an analysis of the factors that contribute to producti-vity growth, such as innovation, technology, and investments in education and training. The industries that have contributed to productivity growth in North Macedonia include the information technology sector, the production of goods and services, as well as the agricultural sector. The Services Sector includes tourism, banking, and other services. There has been noticeable productivity growth due to investments in infrastructure and new services. The Industrial Sector, particularly manufacturing, has demonstrated productivity growth due to process modernization and the adoption of new technologies. This has helped increase efficiency and reduce costs. The Agricultural Sector faces significant challenges in terms of productivity due to the use of traditional techniques and a lack of investment. However, there is potential for growth if more investments are made in modern technology and farmer training.